Perbedaan Kadar Kuersetin pada Propolis di Pasaran Wilayah Surakarta - P, Rizky Amalia; Prasetyo, Diding Heri; H, Sri Hartati (Nexus Biomedika, 2012)
Background: Quercetin is one of the active substances in propolis which has many benefits for human health as antioxidant, anticancer, antiallergy, cardioprotector, gastroprotector, lowering blood pressure, and increase the body immunity. Quercetin content in propolis is influenced by geographical factors, differences in the season, climate, plants, bees, and the type of solvent. This study aims to determine differences of quercetin levels of propolis in the market area of ââSurakarta. Methods: This study uses observational analytic methods. Samples of propolis were sold in the market area of ââSurakarta. Sampling was done by purposive sampling as many as six brands of propolis which is divided into 6 groups: P1, P2, P3, P4, P5, and P6. Each group was measured five times. Determination of quercetin in propolis by using UV-Vis spectrophotometer method of Prussian Blue. Data were analyzed for quercetin levels with one-way ANOVA statistical test using the computer program SPSS 17 for windows. Results: Average of quercetin levels of propolis samples obtained results P1 = 9.4440 Â± 0.06465 Âµg/mL, P2 = 4.4760 Â± 0.08591 Âµg/mL, P3 = 10.2700 Â± 0.04000 Âµg/mL, P4 = 7.4120 Â± 0.06648 Âµg/mL, P5 = 8.6780 Â± 0.03347 Âµg/mL, P6 = 8.4960 Â± 0.10877 Âµg/mL withÂ  p < 0.001. Conclusion: There are differences of quercetin levels of propolis in the market area of ââSurakarta. Keywords: Propolis, quercetin levels, UV-Vis spectrophotometer, Prussian BlueÂ